Genital chlamydial infection among women in Nicaragua: validity of direct fluorescent antibody testing, prevalence, risk factors and clinical manifestations. Issue 1 (February 1996) - Herrmann, B; Espinoza, F; Villegas, R R; Smith, G D; Ramos, A; Egger, M
Abstract : OBJECTIVE: To validate the performance of a direct fluorescence antibody (DFA) test and to determine the prevalence, risk factors and clinical manifestations of cervical chlamydia infection in different groups of women in Nicaragua. STUDY POPULATION: 926 women, 863 routine clinic attenders (mean age 27 years) and 63 sex workers (mean age 25 years) attending health centres in León, Corinto, Matagalpa and Bluefields. METHODS: Cervical specimens were examined using the Syva MicroTrak test system with a cut-off of 10 or more elementary bodies (EBs). The DFA results were validated by a one-step polymerase chain reaction (PCR) assay. Discordant results were further examined in nested PCR assays directed at two different target genes. An interviewer-administered questionnaire and a standard gynaecological examination were completed. RESULTS: Sensitivity of DFA was 80.1%, specificity 98.3%, and positive and negative predictive values 62.5% and 99.3%, respectively. Values were lower in locations where samples thawed because of electricity breaks and higher among sex workers. The majority of discordant results was confirmed as positive in nested PCR assays. Prevalence of cervical chlamydia infection based on positivity in DFA and/or PCR ranged from 2% among routine clinic attenders aged 35 years or older, to 8% among adolescent clinic attenders, and to 14% among sex workers. Among routine clinic attenders, young age (odds ratio [OR] 3.6, 95% confidence intervals [95% CI] 1.4-8.9 for women aged 15-19 years as compared with 1 in women 25 years of age or older) and use of oral contraceptives (OR 4.0, 95% CI 1.7-9.6) were the only statistically significant risk factors identified in multivariate logistic regression analysis. Presence of mucopurulent cervical discharge (OR 5.9, 95% CI 3.0-11.5) and presence of ectropion (OR 2.6, 95% CI 1.1-6.5) were the clinical signs independently associated with infection. CONCLUSIONS: Our results indicate that the DFA test was sensitive and specific while the performance of the PCR assay depends on adequate storage of samples. Genital C trachomatis infection is a common health problem among women in Nicaragua. The wide implementation of syndromic STD management algorithms together with health education programmes aimed at young people is the most promising approach to control STD in Nicaragua.